ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DI KELAS VIII A SMP NEGERI 3 SEKAYAM KABUPATEN SANGGAU - Kristinova, Maria; Sowinangun, Suryadi; ., Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: This thesis is titled, "Analysis of Factors Learning Difficulties Students At IPS Integrated Lesson In Class VIII A Junior High School 3Sekayam the District", with, a common problem "What are the factors that cause learning difficulties of students in integrated social studies ".The method used is descriptive survey form. Population of 22 students. The factors that lead to student learning difficulties are internal factors consist of the student's interest at 46.67%, 53.33% motivation, attitude of 16.67%, and 13.33% health. External factors derived from the family way parents educate 26.67%, the relationship of parents with children 40%, family atmosphere / home rate of 13.33%, and 43.33% family economic circumstances. External factors of the school environment consists of factors that come from teachers teaching teachers include 26.66%, 73.33% delivery methods, attendance of teachers 40%. External factors of the society include 53.33% of mass media, friends hang out 50%, and is active in community activities 10%. Keywords: Factors Student Learning Difficulties. Abstrak: Skripsi ini berjudul, Analisis Faktor-faktor Kesulitan Belajar Siswa Pada Mata Pelajaran IPS Terpadu Di Kelas VIII A SMP Negeri 3Sekayam Kabupaten Sanggau, dengan, masalah umum Apa saja faktor-faktor yang menyebabkan kesulitan belajar siswa pada mata pelajaran IPS Terpadu. Metode yang digunakan adalah deskriptif dengan bentuk survei. Populasi berjumlah 22 siswa. Faktor-faktor yang menyebabkan kesulitan belajar siswa yaitu faktor internal terdiri dari minat siswa sebesar 46,67%, motivasi 53,33%, sikap 16,67%, dan kesehatan 13,33%. Faktor eksternal berasal dari lingkungan keluarga cara orang tua mendidik sebesar 26,67%, hubungan orang tua dengan anak 40%, suasana keluarga/rumah sebesar 13,33%, dan keadaan ekonomi keluarga 43,33%. Faktor eksternal dari lingkungan sekolah terdiri dari faktor yang berasal dari guru mencakup cara mengajar guru 26,66%, metode penyampaian materi 73,33%, kehadiran guru 40%. Faktor eksternal dari lingkungan masyarakat mencakup media massa 53,33%, teman bergaul 50%, dan aktif dalam kegiatan masyarakat 10%. Kata Kunci : Faktor-Faktor Kesulitan Belajar Siswa.